Legal Protection for the E-Auction System for the Purchase of Pledge Objects at Office Services and State Wealth Auctions (KPKNL) in an Islamic Perspective - Helena Margaret (Legal Spirit, 2023)
Indonesia is known as a country whose people experience many problems related to debt receivables. However, education regarding collateral rights is still minimal. Therefore  , the government provides solutions related to education on the auction of objects through socialization.  The purpose of  this study discusses  the  process and protection of  legal certainty related to E-Aution of purchasing pawn objects at the  KPKNL service seen in its Islamic perspective.   This type of research     is qualitatively narrative by examining various literature to be discoping into research results. Thereason  is,  there is  socialization related to E-Auction because there is still minimal trust from  the E-Auction  system.  It was seen that  there were many cases of   irresponsible auctions and plus the  majority of Indonesians were Muslims, so the KPKNL  office provided progress from collaboration between managers  Syar'i-based  which is still categorized as new. However,  the collaboration process  between KPKNL and BSI fosters confidence and trust if  the implementation of  the E-Auction  is in accordance with Minister  of Finance Regulation No.  106 / PMK.  06/  2013 on E-Auction and No. 93/PMK. 06/2010 i.e.   preventive protection of auction winners